Vascular factors in Alzheimer's disease - Gustafson, Deborah (Henry Stewart Talks, 2010)
Obesity is the cornerstone of vascular risk, Vascular risk is associated with dementia and Alzheimer's Disease (AD), Hypertension, Overweight and obesity, Cholesterol, Type 2 diabetes, Genetics of dementia point to vascular risk, AD neuropathology is related to vascular risk, AD Prevention, Vascular risk is related to dementia over the life course